The potential of using bacteriophages targeting Salmonella Dublin in cattle herds - Jespersen, Sarah Grønlund; Lutz, Veronika Theresa; Poulsen, Louise Ladefoged; Brøndsted, Lone (Frontiers in Microbiology, 2025)
Salmonella Dublin causes severe illness in cattle and humans and can persistently infect cattle herds for years despite comprehensive control efforts. Bacteriophages are viruses that specifically kill bacteria. This paper reviews existing research and discusses the clinical challenges, applications, and research gaps that need to be addressed to explore the potential of bacteriophages in controlling Salmonella Dublin in cattle herds. Phages targeting Salmonella Dublin have not been systematically isolated for phage therapy applications. However, a few phages infecting Salmonella Dublin have been identified and characterized, showing promising survival in conditions relevant to feed and cattle. Still, detailed information about receptors, host range, phage resistance, and co-evolution of phages targeting Salmonella Dublin is lacking, but is essential for rational cocktail design. The advantages of phage therapy include its high specificity and narrow host range, which leaves the beneficial microbiota of the animal unharmed. The high clonality of Salmonella Dublin within a geographic area can inform the design of targeted phage treatments for different regions. Although the intracellular nature of Salmonella Dublin presents a challenge, phages have been shown to internalize at varying rates depending on their size and type. In conclusion, bacteriophages show promise against Salmonella Dublin, but the development of specific, well-characterized phages and optimized administration approaches is necessary for phage therapy to realize its full potential.